Catita de K-Ximbinho na interpretação do saxofonista Zé Bodega: aspectos híbridos entre o choro e o jazz - Bernardo Vescovi Fabris (2005)
Study about the recognition of musical elements derived from jazz and choro in the music Catita of Sebastião de Barros, known as K-Ximbinho (1917-1980), and performed by the tenor saxophonist José Araújo, known as Zé Bodega (1923-2003), recorded in the album Saudades de Um Clarinete. The analysis of the leadsheet of the music and its recording were related to historical and theoretician references about the performance of choro (ALMEIDA, 1999; SANTOS, 2001) and jazz (GRIDLEY, 1987; HENRY, 1981). The mutual influence between the identified musical elements didnt prevent the work to be recognized as a choro, but indicates a very common musical practice in the field of instrumental Brazilian music, perceived in its composition and performance, witch is the mixing between distinct ways to produce popular music without necessarily creating a new musical gender. This work also presents a transcription of Zé Bodegas solo on Catita, and the leadsheet of Catita that had its harmony reviewed.